Income Analysis in Increasing Business Profits at MSMEs Seblak Bandung Slowdown Karawang - Hoeriah, Hoeriah; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (West Science Business and Management, 2024)
Culinary developments are currently of great interest to the public, one of which is the spicy food seblak, seblak has many fans from adults to children. The researcher's aim is to find out and analyze the income received at UMKM Seblak Bandung Slowdown Karawang in order to increase business profits. In this research, quantitative descriptive methods were used as research methods in the form of observations, interviews, documents and journals. From the data that has been calculated, business profits during one period experienced increases and decreases each month with an average income of Rp. 151,296,212 from January to December 2023 and get an average operating profit of Rp. 112,240,462 per year. In February and March profits increased by 15%, from April to May operating profits increased by 141%, from August to September profits increased by 22%, and from November to December profits increased by 17%, operating profits increased four times in one annual period 2023. In February and March profit growth increased by 15%, from April to May operating profit increased by 141%, from August to September profit increased by 22%, and from November to December Profit increased by 17% as seen from income and expenditure data. If income increases, operating profit also increases, and if operational expenses increase but income is greater than expenses, it does not affect operating profit.